2016
DOI: 10.3390/f7010021
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure, Biodiversity, and Ecosystem Services in Treeline Whitebark Pine Communities: Potential Impacts from a Non-Native Pathogen

Abstract: Whitebark pine (Pinus albicaulis) has the largest and most northerly distribution of any white pine (Subgenus Strobus) in North America, encompassing 18˝latitude and 21˝longitude in western mountains. Within this broad range, however, whitebark pine occurs within a narrow elevational zone, including upper subalpine and treeline forests, and functions generally as an important keystone and foundation species. In the Rocky Mountains, whitebark pine facilitates the development of krummholz conifer communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 64 publications
(117 reference statements)
3
61
2
Order By: Relevance
“…However, the prevalence of P. albicaulis as a tree island initiator is generally predicted by its high relative abundance as a solitary tree, which may result from seed dispersal by Clark's nutcrackers to protective microsites at treeline and greater seedling hardiness. In fact, Tomback et al (2016) found that the proportional abundance of P. albicaulis among solitary trees in the ATE across 10 study areas predicted its proportional abundance as a tree island initiator.…”
Section: Evaluating P Albicaulis Leeward Micrositesmentioning
confidence: 95%
“…However, the prevalence of P. albicaulis as a tree island initiator is generally predicted by its high relative abundance as a solitary tree, which may result from seed dispersal by Clark's nutcrackers to protective microsites at treeline and greater seedling hardiness. In fact, Tomback et al (2016) found that the proportional abundance of P. albicaulis among solitary trees in the ATE across 10 study areas predicted its proportional abundance as a tree island initiator.…”
Section: Evaluating P Albicaulis Leeward Micrositesmentioning
confidence: 95%
“…Previous studies show P. albicaulis to be the most prevalent solitary tree in many, but not all Rocky Mountain treeline communities (Tomback et al. , ). For 10 study areas across the Rocky Mountain distribution of P. albicaulis , Tomback et al.…”
Section: Introductionmentioning
confidence: 95%
“…; Tomback et al. , ). Tree island initiation involves the initial establishment of an isolated or solitary krummholz conifer followed over time by the establishment of other conifers in its lee.…”
Section: Introductionmentioning
confidence: 98%
“…Some research results showed that agrochemical treatments (especially pesticide an fertilizer) had caused problem social and environmental changes (Altieri et al, 1984;Altieri, 1999;Scherret al, 2008). Agricultural and forestry environment managements are keys for conservation of diversity which significantly improve richness and abundances of species, while tree able to reduce able to improve pest, pathogen incidence, and also to provide ecology services in strengthening beneficial insects (Batary et al, 2011;Tomback et al, 2016;Aluja et al, 2014).…”
Section: Introductionmentioning
confidence: 99%